PENGARUH EARNING PER SHARES (EPS), LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PERUSAHAAN : (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2018 – 2020) - Yogi Ginanjar; Apriliani (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
Stock returns are the results obtained from investments made by investors. This study aims to determine the effect of Earning Per Shares (Eps), Leverage, and Firm Size on Stock Returns in banking companies listed on the Indonesia Stock Exchange (IDX) from 2018-2020. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) from 2018-2020, totaling 43 companies. The sampling in this study used a purposive sampling technique where the sample that met the criteria were 20 banking companies listed on the Indonesia Stock Exchange (IDX) with a period of 3 years so that the total data in this study were 60 data. The data analysis technique used in this research is descriptive analysis of Verification analysis through classical assumption test of multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing, namely t test and f test. The analytical tool used in this study is using the SPSS 25 program. The results show that Earning Per Shares (EPS) has an effect on stock returns, Leverage has no effect on stock returns, and Firm size has no effect on stock returns. Earning Per Shares (EPS), Leverage, and Firm Size have an effect on Stock Return.